Going remote : how the flexible work economy can improve our lives and our cities - Kahn, Matthew E., 1966- (University of California Press, 2022)
"A leading urban economist's hopeful study of how shifts to remote work can change all of our lives for the better. As Covid-19 descended upon the country in 2020, millions of American office workers transitioned to working from home to reduce risk of infection and prevent spread of the virus. In the aftermath of this shift, a significant number of workers will remain at least partially remote. It is clear that this massive experiment we were forced to run will have long-term consequences, changing the shape of our personal and work lives, as well as the urban landscape around us. How will the rise of telecommuting affect workers' quality of life, the profitability of firms, and the economic geography of our cities and suburbs? Going Remote addresses the uncertainties and possibilities of this moment. In Going Remote, urban economist Matthew E. Kahn takes readers on a journey through the new remote work economy, revealing how people will configure their lives when they have more freedom to choose where they work and how they live. Melding ideas from labor economics, family economics, the theory of the firm, and urban economics, Kahn paints a realistic picture of what will happen to workers, firms, and urban areas, big and small. As Kahn shows, the rise of remote work presents especially valuable opportunities for flexibility and equity in the lives of women, minorities, and young people, and even for those whose jobs do not allow them to work from home. Uncovering the key implications for our quality of life, Going Remote demonstrates how the rise of remote work can significantly improve the standard of living for millions of people by expanding personal freedom, changing the arc of how we live, work, and play"--